SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB DI SD NEGERI 01 WINDUAJI - Ajeng; Ahmad Faizin; Abdul Jamil (Politeknik Negeri Indramayu, 2023)
The library is a facility owned by educational institutions in their service efforts in the field of education. The role of the library is very important in providing scientific books for students and teachers in an effort to provide maximum service. In today's digital era, books have switched to media, which initially only consisted of sheets of paper and now in the form of digital images or writing. In the library information system, usually in recording using sheets of paper in the form of books, for example book data, borrowing data and others. By using a system that is still manual, there will be a risk of data loss and damage to the ledger, in the process of searching the data it also takes a long time. It will be easier and more practical when the information system is managed well computerized. SDLC is the method used to build a library information system at SD Negeri 01 winduaji because this method is effective and efficient in its implementation. The web-based library information system includes member masters, book masters, transactions, reports, fines and officers who later can input all data using a computerized system to make it easier for librarian. System testing carried out using blackbox testing by Mr. Adimas as the library manager at SD Negeri 01 Winduaji proves that the library information system at SD Negeri 01 Winduaji can run well with a percentage gain of 90% for its success and it is hoped that the management system created can ease the management of the library in SD Negeri 01 as in the master members, master books, transactions, reports, fines and officers at SD Negeri 01 Winduaji.